Donation After Circulatory Death Is Associated With Similar Posttransplant Survival in All but the Highest‐Risk Hepatocellular Carcinoma Patients. Issue 9 (21st July 2020) - Silverstein, Jordyn; Roll, Garrett; Dodge, Jennifer L.; Grab, Joshua D.; Yao, Francis Y.; Mehta, Neil
Abstract : Liver transplantation (LT) recipients with hepatocellular carcinoma (HCC) receive a higher proportion of livers from donation after circulatory death (DCD) donors compared with non‐HCC etiologies. Nevertheless, data on outcomes in patients with HCC receiving DCD grafts are limited. We evaluated the influence of DCD livers on post‐LT outcome among HCC patients. We identified 7563 patients in the United Network for Organ Sharing (UNOS) database who underwent LT with Model for End‐Stage Liver Disease score exceptions from 2012 to 2016, including 567 (7.5%) who received a DCD donor organ and 6996 (92.5%) who received a donation after brain death (DBD) donor organ. Kaplan‐Meier probabilities of post‐LT HCC recurrence at 3 years were 7.6% for DCD and 6.4% for DBD recipients ( P  = 0.67) and post‐LT survival at 3 years was 81.1% versus 85.5%, respectively ( P  = 0.008). On multivariate analysis, DCD donor (hazard ratio, 1.38; P  = 0.005) was an independent predictor of post‐LT mortality. However, a survival difference after LT was only observed in subgroups at higher risk for HCC recurrence including Risk Estimation of Tumor Recurrence After Transplant (RETREAT) score ≥4 (DCD 57.0% versus DBD 72.6%; P  = 0.02), alpha‐fetoprotein (AFP) ≥100 (60.1% versus 76.9%; P  = 0.049), and multiple viable tumors on last imaging before LT (69.9% versus 83.1%; P  = 0.002). In this analysis of HCC patients receiving DCD versus DBD livers in the UNOS database, we found that patients with a low‐to‐moderate risk of HCC recurrence (80%‐90% of the DCD cohort) had equivalent survival regardless of donor type. It appears that DCD donation can best be used to increase the donor pool for HCC patients with decompensated cirrhosis or partial response/stable disease after locoregional therapy with AFP at LT <100 ng/mL.